Natural Language Processing in Medicine: An Overview - Spyns, P. (Methods of Information in Medicine, 1996)
An overview is given of natural language processing applications in medicine. An attempt has been made to enumerate the most important and known international projects and to summarize their goals, principles, methods and results. A section is devoted to projects involving the Dutch language. A more general discussion about the two fundamental approaches concerning medical language understanding is provided. An extensive bibliography may be useful for those wishing to explore this research domain.
Keywords: Natural Language Processing; Computational Linguistics; Medical Language Understanding